Ablation of Progenitor Cells Does Not Impede Motor Recovery or Diminish Cognitive Function Following a Focal Cortical Stroke - Lee, Karah S.H. (Université d'Ottawa / University of Ottawa, 2016)
Following a stroke there is a significant increase in the number and migration of progenitor cells (PCs) to the infarct, and positive correlations between neurogenesis and recovery. Loss-of-function studies have conflicting findings on whether the ablation of PCs impedes motor or cognitive function post-stroke. This thesis examines if neurogenesis per se is required for motor recovery and spatial learning and memory. PCs were ablated in an adult GFAP-TK rat model that allows for the inducible deletion of GFAP-expressing PCs in the brain. An endothelin-1 (ET-1) stroke was produced and assessment of motor function and spatial learning and memory revealed no differences between control and GFAP-TK rats in which PCs were ablated. This study is the first to use a focal cortical stroke model in a rat to study PCs and stroke recovery, and suggest that PCs and their progeny are dispensable for motor recovery and spatial learning and memory post-stroke.
Keywords: Adult neurogenesis; Stroke; Transgenic; Rat